OPPORTUNITIES FOR ETHNIC TOURISM IN UZBEKISTAN (World Economics and Finance Bulletin, 2024)
This work is devoted to the disclosure of the concept of such a relatively young direction of international tourism as ethnic tourism. The ethnic prerequisites for the development of international tourism are that our planet is inhabited by a large number of different peoples, each of which has its own history, culture, traditions, customs, and religion. Many people, due to the growth of the educational and cultural level, strive to get acquainted with the life of different peoples to the fullest extent. This can only be achieved by visiting foreign countries. Thus, international ethnic tourism is a means of learning about the life of other peoples